Scriptura Scripturam Interpretatur [scripture interprets scripture]: an analysis of the Arabic Bible as used in the Tafsīrs of Ibn Barrajān (d. 536/1141) and al-Biqāʿī (d. 885/1480) - McCoy III, RM (2019)
The Bible remains an indispensable part of the Muslim tradition as a scripture with which the Qurʾān is in close dialogue. From the earliest period of qurʾānic interpretation, questions concerning the exact nature of the Bible and its relationship to the Qurʾān provoked classical Muslim scholars to either defend the text or condemn it for the sake of their own sacred book and prophet. Recent scholarship on Ibn Barrajān (d. 536/1141) and al-Biqāʿī (d. 885/1480) has provided fertile ground for cultivating new perspectives on the relationship between qurʾānic and biblical hermeneutics within tafsīr studies. This dissertation further tills this ground by exploring Ibn Barrajān’s method of qurʾānic interpretation, known as naẓm al-qurʾān, and that of al-Biqāʿī, called ʿilm al-munāsabāt, and by examining how the Arabic Bible is used in their reading of the Qurʾān. Moreover, this exploration is facilitated through an original comparative analysis between the two authors’ biblical quotations and several Arabic Bible manuscripts believed to have circulated in the milieux of Ibn Barrajān and al-Biqāʿī. How each author transmits and integrates biblical material into their tafsīr will shed light on the reception history of the Bible in the Islamic tradition. Therefore, whether their citations remain true to the biblical source text or, rather, become an islamicised version of the Bible is of primary importance to discover.